In focus : functional anatomy [ (VEA Australia Pty Ltd, 2003)
Our bodies perform an amazing variety of functions. Elite athletes often amaze us with astonishing feats of physical skill, dexterity and endurance. Underneath the skin are bones, muscles, tendons, ligaments, organs and all other elements of our internal structure. These elements manage to combine their functions at the right time and the right way to produce, for example, the movements required to walk, run, swim or even pole vault. In this program we examine how our anatomy enables us to be physically active. The topic has been split into four body systems; skeletal system, muscular system, respiratory system, and circulation system. Using extensive graphics and sporting footage, this program provide a comprehensive overview of functional anatomy.